Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2008
DOI: 10.1007/s00262-008-0567-5
|View full text |Cite
|
Sign up to set email alerts
|

Targeting 11q23 positive acute leukemia cells with high molecular weight-melanoma associated antigen-specific monoclonal antibodies

Abstract: Background-Acute leukemia with 11q23 aberrations is associated with a poor outcome with therapy. The lack of efficacy of conventional therapy has stimulated interest in developing novel strategies. Recent studies have shown that 11q23-positive acute leukemia cells express the high molecular weight-melanoma associated antigen (HMW-MAA). This tumor antigen represents a useful target to control growth of human melanoma tumors in patients and in severe combined immunodeficient (SCID) mice, utilizing antibody-based… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2009
2009
2015
2015

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 39 publications
0
11
0
Order By: Relevance
“…The primers which were utilized for genomic PCR and sequencing were: JAK2 V617F , forward, 5′ TGAAGCAGCAAGTATGATGAGC3′ and reverse, 5′ ACCTAGCTGTGATCCTGAAACTG3′; JAK2 T875N , forward, 5′ GGTAATTTTGGGAGTGTGGAGA3′, AND REVERSE, 5′ AGCTTACCAGCACTGTAGCACAC3′; MPL W515L/K , forward, 5′ AAGTCTGACCCTTTTTGTCTCCT3′, reverse, 5′ GAGGTGACGTGCAGGAAGTGG3′. PCR was conducted as previously described [22]. …”
Section: Methodsmentioning
confidence: 99%
“…The primers which were utilized for genomic PCR and sequencing were: JAK2 V617F , forward, 5′ TGAAGCAGCAAGTATGATGAGC3′ and reverse, 5′ ACCTAGCTGTGATCCTGAAACTG3′; JAK2 T875N , forward, 5′ GGTAATTTTGGGAGTGTGGAGA3′, AND REVERSE, 5′ AGCTTACCAGCACTGTAGCACAC3′; MPL W515L/K , forward, 5′ AAGTCTGACCCTTTTTGTCTCCT3′, reverse, 5′ GAGGTGACGTGCAGGAAGTGG3′. PCR was conducted as previously described [22]. …”
Section: Methodsmentioning
confidence: 99%
“…The cDNA was used as a template in a PCR reaction to amplify different HSP 70s and the housekeeping gene actin. The reaction was performed as previously described [13]. The primers are described in Table 1.…”
Section: Methodsmentioning
confidence: 99%
“…However, they leave veiled several biological and clinical questions, including the biological significance of the NG2/CSPG4 expression on discrete leukemic cells and the therapeutic potential of this selective expression. The negative outcome of the experimental targeting of a model leukemic cell line with two anti-NG2/CSPG4 antibodies 105 , independently validated as effective tools for abrogating growth and dissemination of solid tumour xenografts ( see below ), reinforces these uncertainties. In parallel, in a recent publication Petrovici et al 106 , reported some AML cases manifesting a normal karyotype, while, concurrently, a significant amount of the leukemic cells expressed NG2/CSPG4.…”
Section: Dismally Fated Leukemic Patients De Novo Express Ng2/cspg4 mentioning
confidence: 99%
“… 1 As established by flow cytometry using the reference mAb 7.1; 2 Adopted average cut-off was >25% of leukemic blasts; 3 NG2/CSPG4 expression has also been documented in one case of DC2/NK cell ALL 105 ; Abbreviations : NS = not specified; ND = not determined. …”
Section: Figurementioning
confidence: 99%